2021
DOI: 10.1177/1470320321995082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic value of the renal resistive index as a marker of the subclinical development of cardiorenal syndrome in MMVD dogs

Abstract: Introduction: Myxomatous mitral valve disease (MMVD) in dogs inevitably causes renal dysfunction. These interactions are known as the cardiorenal syndrome (CRS). The main aims of the study were to evaluate whether renal resistive index (RRI) may be useful as a non-invasive marker in subclinical stage of kidney injury in dogs with MMVD and to compare RRI with SDMA and Cyst C. Methods: Forty-four dogs were divided into two groups: control—15 healthy dogs and the heart group—29 dogs with MMVD (ACVIM class Cc). St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In women, higher systolic blood pressure and body weight were associated with higher RI values, whereas increases in heart rate were associated with lower RI values 52 . Correlations between sex, body weight, heart rate, and systolic blood pressure were not observed in dogs 39,53 . The influence of sex and body weight on the RI of cats is still not clear and only one study reported a positive correlation between body weight and index for the species 39…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In women, higher systolic blood pressure and body weight were associated with higher RI values, whereas increases in heart rate were associated with lower RI values 52 . Correlations between sex, body weight, heart rate, and systolic blood pressure were not observed in dogs 39,53 . The influence of sex and body weight on the RI of cats is still not clear and only one study reported a positive correlation between body weight and index for the species 39…”
Section: Discussionmentioning
confidence: 95%
“…52 Correlations between sex, body weight, heart rate, and systolic blood pressure were not observed in dogs. 39,53 The influence of sex and body weight on the RI of cats is still not clear and only one study reported a positive correlation between body weight and index for the species. 39…”
Section: Discussionmentioning
confidence: 99%
“…As the functions of the heart and kidneys are closely related to fluid regulation, and failure of one organ leads to a loss of function of the other, this condition is termed cardiorenal syndrome (CRS) (Ronco et al 2008). In dogs, renal failure secondary to cardiac disease is also known as CRS (Szczepankiewicz et al 2021). Cardiac output is reduced in dogs with myxomatous mitral valve disease, leading to a decreased GFR and exacerbation of azotaemia (Nicolle et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Szczepankiewicz et al. have reported that RI is useful in detecting kidney injury in dogs with MMVD 14 . However, no study has yet focused on VII and IRVF patterns in dogs.…”
Section: Introductionmentioning
confidence: 99%